Using Pre-Clinical Studies to Explore the Potential Clinical Uses of Exosomes Secreted from Induced Pluripotent Stem Cell-Derived Mesenchymal Stem cells - Andrew Kailin Zhou; Eric Jou; Victor Lu; James Zhang; Shirom Chabra; Joshua Abishek; Ethan Wong; Xianwei Zeng; Baoqiang Guo (Tissue Engineering and Regenerative Medicine, 2023)
Recent studies of exosomes derived from mesenchymal stem cells (MSCs) have indicated high potential clinical applications in many diseases. However, the limited source of MSCs impedes their clinical research and application. Most recently, induced pluripotent stem cells (iPSCs) have become a promising source of MSCs. Exosome therapy based on iPSC-derived MSCs (iMSCs) is a novel technique with much of its therapeutic potential untapped. Compared to MSCs, iMSCs have proved superior in cell proliferation, immunomodulation, generation of exosomes capable of controlling the microenvironment, and bioactive paracrine factor secretion, while also theoretically eliminating the dependence on immunosuppression drugs. The therapeutic effects of iMSC-derived exosomes are explored in many diseases and are best studied in wound healing, cardiovascular disease, and musculoskeletal pathology. It is pertinent clinicians have a strong understanding of stem cell therapy and the latest advances that will eventually translate into clinical practice. In this review, we discuss the various applications of exosomes derived from iMSCs in clinical medicine.